Arbitration By SSOs as a preferred solution for solving the FRAND licensing of SEPs? - LIU, Kung-Chung (Institutional Knowledge at Singapore Management University, 2021)
In the last decade, the licensing of standard essential patents (SEPs) on fair, reasonable and non-discriminatory (FRAND) terms has been a thorny issue for SEP holders in the US and Europe on the one hand, and major SEP implementers in major Asian economies on the other, such as Japan, Korea, the PRC, Taiwan and even India. With the rise of the Fourth Industrial Revolution, driven by the Internet of Things (IoT), 5G, driverless vehicles, and artificial intelligence (AI), which relies even more on interconnectivity, more and more new standards and SEPs will emerge, and the issue of FRAND licensing of SEPs will be even hotter.